1999
DOI: 10.1182/blood.v94.9.3067
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD10 by Human T Cells That Undergo Apoptosis Both In Vitro and In Vivo

Abstract: This study shows that human postthymic T cells express CD10 when undergoing apoptosis, irrespective of the signal responsible for initiating the apoptotic process. Cells from continuous T-cell lines did not normally express CD10, but became CD10+ when induced into apoptosis by human immunodeficiency virus (HIV) infection and exposure to CD95 monoclonal antibody, etoposide, or staurosporin. Inhibitors of caspases blocked apoptosis and CD10 expression. Both CD4+ and CD8+ T cells purified from normal peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(1 citation statement)
references
References 66 publications
1
0
0
Order By: Relevance
“…In agreement with our findings, Ding et al, also reported the use of immobilized CD3 beads followed by treatment with RA that generated a similar distribution of α4β7 + CD4 + T cell subsets that was characterized by a predominantly naive CD4 + T cell phenotype [57]. Earlier reports by Cutrona et al indicated that CD10 expression on T cells could be used to reliably identify cells undergoing apoptosis during cell division [58,59]. Unsurprisingly, we observed elevated expression of CD10 within the TEMRA CD4 + T cells and an increasing trend within the EM CD4 + T cells of RA-induced α4β7 + CD4 + T cells hence accounting for their rapid turnover.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our findings, Ding et al, also reported the use of immobilized CD3 beads followed by treatment with RA that generated a similar distribution of α4β7 + CD4 + T cell subsets that was characterized by a predominantly naive CD4 + T cell phenotype [57]. Earlier reports by Cutrona et al indicated that CD10 expression on T cells could be used to reliably identify cells undergoing apoptosis during cell division [58,59]. Unsurprisingly, we observed elevated expression of CD10 within the TEMRA CD4 + T cells and an increasing trend within the EM CD4 + T cells of RA-induced α4β7 + CD4 + T cells hence accounting for their rapid turnover.…”
Section: Discussionsupporting
confidence: 92%